An Analytical Method of Coulomb’s Active Earth Pressure Acting on Cohesion-Less Backfill Subject to Local Surcharge in Cold Regions - Li Liu; Zhen Yang; Pan Zhou; Hongwei Yang (Advances in Civil Engineering)
The traditional Coulomb’s earth pressure theory does not consider the effect of local surcharge on the lateral earth pressure and its critical failure angle. However, in practice, local surcharges commonly act on the surface of frozen backfill that is affected by freeze-thaw actions in cold regions and tend to affect the active thrust and its position. In paper, analytical solutions for estimating the active thrust, critical wedge failure angle, and action position subject to a local surcharge in cold regions are proposed. Herein, the simplified equivalent moment of surcharge is adopted on the premise of maintaining Coulomb’s earth pressure assumptions. The formula derivation is provided as a typical example to obtain the active thrust, critical wedge failure angle, and its position under a strip surcharge. Compared with previous approaches, the proposed solutions lead to easier evaluation of all indexes associated with Coulomb’s active earth pressure. Meanwhile, the expressions of Coulomb’s earth pressure under other types of nonuniform loading acting on the wall are discussed. In addition, sensitivity is performed to assess the effect of some main parameters. The results indicate that the dip angle of retaining wall-back and the friction angle of frozen backfill soil are two most significant indexes that influence the active thrust and its position.